Development and Utilization of Introgression Lines Using Synthetic Octaploid Wheat (Aegilops tauschii × Hexaploid Wheat) as Donor - Zhang, Dale; Zhou, Yun; Zhao, Xinpeng; Lv, Linlin; Zhang, Cancan; Li, Junhua; Sun, Guiling; Li, Suoping; Song, Chunpeng (Frontiers in Plant Science, 2018)
As the diploid progenitor of common wheat, Aegilops tauschii Cosson (DD, 2n = 2x = 14) is considered to be a promising genetic resource for the improvement of common wheat. In this work, we demonstrated that the efficiency of transferring A. tauschii segments to common wheat was clearly improved through the use of synthetic octaploid wheat (AABBDDDD, 2n = 8x = 56) as a “bridge.” The synthetic octaploid was obtained by chromosome doubling of hybrid F1 (A. tauschii T015 × common wheat Zhoumai 18). A set of introgression lines (BC1F8) containing 6016 A. tauschii segments was developed and displayed significant phenotype variance among lines. Twelve agronomic traits, including growth duration, panicle traits, grain traits, and plant height (PH), were evaluated. And transgressive segregation was identified in partial lines. Additionally, better agronomic traits could be observed in some lines, compared to the recurrent parent Zhoumai 18. To verify that the significant variance of those agronomic traits was supposedly controlled by A. tauschii segments, 14 quantitative trait loci (QTLs) for three important agronomic traits (thousand kernel weight, spike length, and PH) were further located in the two environments (Huixian and Zhongmou), indicating the introgression of favorable alleles from A. tauschii into common wheat. This study provides an ameliorated strategy to improve common wheat utilizing a single A. tauschii genome.